THE EDUCATIONAL VALUE OF THE MUNGGAH MOLO TRADITION IN SUMUB LOR VILLAGE, SRAGI DISTRICT, PEKALONGAN DISTRICT - Salsabila; Sri Prastiti Kusuma Anggraeni (Universitas PGRI Palembang, 2023)
The aim of this research is to describe the form of the munggah molo tradition and the educational values ​​in the munggah molo tradition in Sumub Lor Hamlet, Sragi District, Pekalongan Regency. This research uses a qualitative descriptive method using observation, interview and documentation techniques. The approach used is a folklore approach. The results of this research are that the munggah molo tradition is a tradition that is partly oral, because the munggah molo tradition is a hereditary activity of the people in Sumub Lor Hamlet which is still carried out every time they build a house. The form of the munggah molo tradition is a series of processions, traditions and rituals contained in the munggah molo tradition. The processions include pitung, sitting batur, munggah molo, walimahan. The educational values ​​contained in the munggah molo tradition include, among others, the value of mutual cooperation in the batur sitting procession, the value of caring in the walimahan procession, religious values ​​in the munggah molo procession.